High-Performance Electroactive Polymer Actuators Based on Ultrathick Ionic Polymer Metal Composites with Nanodispersed Metal Electrodes - Wang, Hyuck Sik; Cho, Jaehyun; Song, Dae Seok; Jang, Jong Hyun; Jho, Jae Young; Park, Jong Hyuk (American Chemical Society, 2017)
Ionic polymer metal composites (IPMCs) have been proposed as biomimetic actuators that are operable at low applied voltages. However, the bending strain and generating force of the IPMC actuators have generally exhibited a trade-off relationship, whereas simultaneous enhancement of both the qualities is required for their practical applications. Herein, a significant improvement in both the strain and force of the IPMC actuators is achieved by a facile approach, exploiting thickness-controlled ion-exchange membranes and nanodispersed metal electrodes. To guarantee a large generating force of the IPMC actuators, ultrathick ion-exchange membranes are prepared by stacking pre-extruded Nafion Ems. Metal electrodes with a nanodispersed structure are formed on the membranes via alcohol-assisted electroless plating, which allows increased capacitance and facilitated ion transport. The resulting actuators exhibit greatly enhanced electromechanical properties, including an approximately four times larger strain and two times larger force compared to those of actuators having the conventional structure. Moreover, the ability to lift 16 coins (a weight of 124 g) has been successfully demonstrated using ultrathick IPMC actuators, which shows great promise in realizing artificial muscles.
Keywords: ARTIFICIAL MUSCLES; BIOMIMETIC SENSORS; IPMC ACTUATORS; MEMBRANE